Moise și Iisus Hristos – „Profetul” (Dt 18,15) - Chirilă, Ioan (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Within Judaism, prophetism reveals to the world its eschatological meaning, God’s will in relation to man and creation. Prophetic themes related to Christology, soteriology and eschatology are introduced and contained in the Torah, developed in the other books of the Old Testament and find their fulfilment in the New Testament. The present study aims to demonstrate this by comparing a prophet (Moses) with Christ, the Supreme Prophet. This comparison includes some elements of Jewish prophetism, which is realized in the work of the Supreme Prophet. In Deuteronomy 18:15, 18-19, the Supreme Prophet, the Saviour Jesus Christ, is announced. He is distinguished from the Old Testament prophet (Isaiah 7:1-2) because he is God, he is the Word who proclaims and who is self-evident. In the New Testament, both Jesus’ words (Matthew 7:29; Luke 24) and actions (Matthew 4:23; Luke 7:22) highlight Jesus’ prophetic activity in which he communicates God’s will absolutely and completely.